Reconociendo la autoconstrucción como base de apropiación espacial del hábitat doméstico: propuesta de vivienda colectiva progresiva (2021)
This Degree Project investigates the issue of "progressivity" in housing as a way of providing habitability to its users since they have the ability to supply not only a basic need to access a shelter and a roof but also to provide comfort and wellness. In the same way, it is evident in the context of self-built housing, which, in response to the needs and possibilities of its inhabitants, is transformed as its owners do, however, there is not enough information about these dynamics of change in the context of self-built housing in informal settlements in Neiva. Given the great family diversity of today and the new dynamics in family